ESCAPE: An Open-Label Trial of Personalized Immunotherapy in Critically lll COVID-19 Patients - Eleni Karakike; George N. Dalekos; Ioannis Koutsodimitropoulos; Maria Saridaki; Chryssa Pourzitaki; Georgios Papathanakos; Antigone Kotsaki; Stamatios Chalvatzis; Vasiliki Dimakopoulou; Nikolaos Vechlidis; Elisabeth Paramythiotou; Christina Avgoustou; et al. (Karger Publishers, 2021)
Background: Macrophage activation-like syndrome (MALS) and complex immune dysregulation (CID) often underlie acute respiratory distress (ARDS) in COVID-19. We aimed to investigate the effect of personalized immunotherapy on clinical improvement of critical COVID-19. Methods: In this open-label prospective trial, 102 patients with ARDS by SARS-CoV-2 were screened for MALS (ferritin >4,420 ng/mL) and CID (ferritin ≤4,420 ng/mL and low human leukocyte antigen (HLA)-DR expression on CD14-monocytes). Patients with MALS or CID with increased aminotransferases received intravenous anakinra; those with CID and normal aminotransferases received tocilizumab. The primary outcome was ≥25% decrease in the Sequential Organ Failure Assessment (SOFA) score and/or 50% increase in the respiratory ratio by day 8; 28-day mortality, change of SOFA score by day 28, serum biomarkers, and cytokine production by mononuclear cells were secondary endpoints. Results: The primary study endpoint was met in 58.3% of anakinra-treated patients and in 33.3% of tocilizumab-treated patients (p: 0.01). Most patients in both groups received dexamethasone as standard of care. No differences were found in secondary outcomes, mortality, and SOFA score changes. Ferritin decreased among anakinra-treated patients; interleukin-6, soluble urokinase plasminogen activator receptor, and HLA-DR expression increased among tocilizumab-treated patients. Survivors by day 28 who received anakinra were distributed to lower severity levels of the WHO clinical progression scale. Greater incidence of secondary infections was found with tocilizumab treatment. Conclusion: Immune assessment resulted in favorable anakinra responses among critically ill patients with COVID-19 and features of MALS.